(untitled) (Annual of the Faculty of Philosophy in Skopje, 2014)
The text analyses the ethno-demogi^aphic changes that have occurred in the part of Macedonia which after the Balkan and the First World War became integral part of Kingdom Serbia, i.e. Kingdom SHS/Yugoslavia. The analysis of the mentioned changes is supported by the official statistic data published after 1914, based on the population census conducted by the Kingdom Serbia in 1913 and by the Kingdom SHS/Yugoslavia in 1921 and 1931. Apart from the data from the official census publications as very significant source for the migration movements, also used are several field ethnographic and anthropogeography researches. Based on the analysis of the official statistic data and the migration movements, we can see the changes in the ethno demographic structure of the population in the part of Macedonia under Serbian occupation, especially in the period between the two world wars.